The gut-lung axis: Gut microbiota changes associated with pulmonary fibrosis in mouse models induced by bleomycin - Quan, Yunyun; Yin, Zhujun; Chen, Shilong; Lang, Jirui; Han, Liyang; Yi, Jing; Zhang, Lu; Yue, Qianhua; Tian, Weiwei; Chen, Ping; Du, Shenglin; Wang, Jianbo; et al. (Frontiers in Pharmacology, 2022)
The main objective of this study was to research on the alterations in the gut microbiota (GM) of pulmonary fibrosis (PF) mice induced by bleomycin (BLM) with its underlying mechanism. BLM was docked with the targets of TGF-β/SMAD and Caspase-3 pathways, respectively by using molecular docking technique. The H&E staining and Masson staining were applied to observe the histopathological changes in the pulmonary tissue. The detection of the apoptotic signals was conducted by flow cytometry. The mRNA expression of targets involved in TGF-β/SMAD and Caspase-3 signaling pathways in lungs were determined by qPCR. 16S rDNA sequencing analysis was used to investigate the changes of GM in fecal samples of mice in each group. The results turned out that PF mechanism of BLM was to cause apoptosis of lung tissue cells such as alveolar epithelial cells resulting in destroyed alveolar structure, and excessive production of extracellular matrix (ECM), which were related to activating TGF-β/SMAD and Caspase-3 pathways. As for the GM, it was found that after BLM inducing PF in mice, the micro ecological balance of GM was destroyed; the distance of PCo1 and PCo2 was elongated; and the relative abundance of some intestinal probiotics like Catenibacterium and Lactobacillus (Lactobacillus johnsonii and Lactobacillus gasseri) were dramatically lowered; the relative abundance of Verrucomicrobiales and Enterobacteriales were substantially increased. The gut-lung axis suggests that GM changes associated with PF in mouse models induced by BLM.